On the move: globalising higher education in Europe and beyond. Issue 3 (2nd July 2016) - Robertson, Susan L.; Kedzierski, Matt
Abstract : This paper examines the rise and rise of a range of individual, institutional, national and regional mobility projects in the global higher education sector, and explores the implications of these dynamics for the economisation, and thus instrumentalisation, of English as a global language, as a medium of instruction and a competitive advantage. Yet we also point to new counter-tendencies at play, including the rise of China as an education exporter, and promoter of Chinese soft-power through the Confucius Institutes. Along with changes in Western labour markets that might well alter what has been to date a Eurocentric set of flows, this suggests a dynamic and changing landscape. We conclude by pointing to the tensions and contradictions in a changing higher education landscape and the issues this generates for those cultural and civilisation projects that languages are constitutive of.